간호·간병통합서비스병동 간호사의 간호전문직 자부심과 역할갈등이 인간중심돌봄에 미치는 영향 - 이슬기 (The Graduate School, Ajou University, 2024)
본 연구는 간호·간병통합서비스병동 간호사의 간호전문직 자부심, 역할갈등, 인간중심돌봄의 정도를 확인하고 인간중심돌봄에 영향을 미치는 요인을 파악하기 위한 횡단적 조사연구이다._x000D_ 본 연구는 2023년 4월 14일부터 4월 24일까지 수원시 소재의 1개의 상급종합병원에서 근무하는 간호·간병통합서비스병동 간호사 137명을 대상으로 구조화된 자가보고식 설문지를 이용하여 자료수집 하였다._x000D_ 간호·간병통합서비스병동 간호사의 간호전문직 자부심은 전재희, 이은희, 김은주(2020)가 개발한 간호사의 전문직 자부심 도구를 사용하였고, 역할갈등은 이은희, 조경숙, 손행미, 이여진, 유정숙(2013)이 간호사를 대상으로 개발한 역할갈등 도구를 사용하여 측정하였으며, 인간중심돌봄은 Slater, McCance, & McCormack(2017)이 개발한 Person-centered Practice Inventory–Staff(PCPI-S)을 김소현, 탁성희(2021)가 한국어로 번안한 후 신뢰도와 타당도를 검증한 한국어판 인간중심돌봄 측정도구를 사용하여 측정하였다. 수집된 자료는 SPSS 23.0 프로그램을 이용하여 기술통계, Independent t-test, ANOVA, Scheffe, Pearon's correlation coefficient, Multiple regression으로 분석하였다. _x000D_ _x000D_ 본 연구의 주요 결과는 다음과 같다._x000D_ 1. 연구대상자의 간호전문직 자부심은 135점 만점에 평균 90.68±12.13점, 역할갈등은 328점 만점에 101.92±39.58점, 인간중심돌봄은 255점 만점에 175.37±19.75점으로 나타났다. _x000D_ 2. 연구대상자의 일반적 특성에 따른 인간중심돌봄은 연령(F=5.365, p=.006), 결혼 상태(t=-2.850, p=.005)에 따라 통계적으로 유의한 차이가 있는 것으로 나타났다. _x000D_ 3. 연구대상자의 인간중심돌봄은 간호전문직 자부심(r=.312, p<.001)과 유의한 양의 상관관계가 있는 것으로 나타났고, 역할갈등(r=-.413, p<.001)은 간호전문직 자부심과 유의한 음의 상관관계가 있는 것으로 나타났다. _x000D_ 4. 연구대상자의 인간중심돌봄에 미치는 요인을 파악한 결과, 결혼상태(β=.226, p=.009), 간호전문직 자부심(β=.293, p=.001)으로 나타났고, 해당 분석 모델의 설명력은 13.4%였다._x000D_ _x000D_ 이상의 연구결과를 바탕으로 간호·간병통합서비스병동 간호사의 인간중심돌봄을 향상시키기 위하여 간호전문직 자부심의 중요도와 필요성에 대해 인식시키고 도모할 수 있는 교육프로그램 개발 및 운영이 필요하며, 근거 제시를 통해 간호서비스의 질을 향상 시킬 수 있는 실질적인 전략 개발이 필요할 것으로 사료된다.|This study is a cross-sectional research study to determine the level of nursing professional pride, role conflict, and person-centered care among nurses in the comprehensive nursing care wards, and to identify factors affecting person-centered care._x000D_ This study collected data from April 14 to April 24, 2023, using a structured self-report questionnaire targeting 137 nurses in the nursing/nursing integrated service ward working at a tertiary general hospital in Suwon-si. ._x000D_ The nursing professional pride in the comprehensive nursing care wards was assessed using the nurses' professional pride tool developed by Jeon Jae-hee, Lee Eun-hee, Kim Eun-ju(2020), and role conflict was measured using the role conflict tool developed for nurses by Lee Eun-hee, Cho Gyeong-sook, Son Haeng-mi, Lee Yeo-jin and Yoo Jeong-sook(2013), and person-centered care was measured using a Korean version of the Person-centered Practice Inventory–Staff (PCPI-S) developed by Slater, McCance, & McCormack (2017), which was verified the reliability and validity after translation into Korean by Kim So-Hyun and Tak Seong-Hee(2021). The collected data were analyzed using descriptive statistics, Independent t-test, ANOVA, Scheffe, Pearon's correlation coefficient, and multiple regression using SPSS 23.0 program._x000D_ _x000D_ The main results of this study are as follows._x000D_ 1. The subject's pride in the nursing profession averaged 90.68±12.13 points out of 135 points, role conflict was 101.92±39.58 points out of 328 points, and person-centered care was 175.37±19.75 points out of 255 points._x000D_ 2. Person-centered care according to the subject's general characteristics was found to have statistically significant differences depending on age (F=5.365, p=.006) and marital status (t=-2.850, p=.005)._x000D_ 3. The subject's person-centered care was found to have a significant positive correlation with nursing professional pride(r=.312, p<.001), and role conflict was found to have a significant negative correlation with nursing professional pride(r=-.413, p<.001)._x000D_ 4. As a result of identifying the factors affecting the subject's person-centered care, it was found that they were marital status (β=.226, p=.009) and nursing professional pride(β=.293, p=.001), and the corresponding analysis model The explanatory power was 13.4%._x000D_ _x000D_ Based on the above research results, it is necessary to develop and operate an educational program that can raise awareness and promote the importance and necessity of nursing professional pride in order to improve the person-centered care of nurses in comprehensive nursing care wards, and It is believed that there is a need to develop practical strategies to improve the quality of nursing services.
학위논문(석사)--간호학과,2024. 2
Keywords: 간호·간병통합서비스병동 간호사; 간호전문직 자부심; 역할갈등; 인간중심돌봄